Detection of Small CYP11B1 Deletions and One Founder Chimeric CYP11B2/CYP11B1 Gene in 11β-Hydroxylase Deficiency - Xie, Hua; Yin, Hui; Ye, Xue; Liu, Ying; Liu, Na; Zhang, Yu; Chen, Xiaoli; Chen, Xiaobo (Frontiers in Endocrinology, 2022)
Objective 11β-Hydroxylase deficiency (11β-OHD) caused by mutations in the CYP11B1 gene is the second common form of congenital adrenal hyperplasia. Both point mutations and the genomic rearrangements of CYP11B1 are important causes of 11β-OHD. However, the high degree of sequence identity between CYP11B1 and its homologous gene CYP11B2, presents unique challenges for molecular diagnosis of suspected 11β-OHD. The aim of this study was to detect the point mutation, indel, small deletion of CYP11B1 and chimeric CYP11B2/CYP11B1 gene in a one-tube test, improving the genetic diagnosis of 11β-OHD. Methods Optimized custom-designed target sequencing strategy was performed in three patients suspected 11β-OHD, in which both the coverage depth of paired-end reads and the breakpoint information of split reads from sequencing data were analysed in order to detect genomic rearrangements covering CYP11B1. Long-range PCR was peformed to validate the speculated CYP11B1 rearrangements with the breakpoint-specifc primers. Results Using the optimized target sequencing approach, we detected two intragenic/intergenic deletions of CYP11B1 and one chimeric CYP11B2/CYP11B1 gene from three suspected patients with 11β-OHD besides three pathogenic heterozygous point mutation/indels. Furthermore, we mapped the precise breakpoint of this chimeric CYP11B2/CYP11B1 gene located on chr8:143994517 (hg19) and confirmed it as a founder rearrangement event in the Chinese population. Conclusions Our optimized target sequencing approach improved the genetic diagnosis of 11β-OHD.